2017
DOI: 10.1007/s10639-017-9669-z
|View full text |Cite
|
Sign up to set email alerts
|

No name, no game: Challenges to use of collaborative digital textbooks

Abstract: Collaborative digital textbooks -comprehensive materials covering entire curriculums -are developing from being books in pdf format to becoming collaborative digital environments where teachers and students can communicate, engage in feedback and discussions, share and manipulate materials, test knowledge, and monitor results. This study investigates how these digital environments are used in school practice: How are the collaborative tools used to improve learning? Thirteen seventh-and eighth-grade classes, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
0
16
0
3
Order By: Relevance
“…In brief, "DTB refers to coherent (digital) material covering entire curriculums, and, if collaborative tools are included, they become collaborative, cDTB". (Grönlund et al 2018).…”
Section: The Development Of New Learning Environmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In brief, "DTB refers to coherent (digital) material covering entire curriculums, and, if collaborative tools are included, they become collaborative, cDTB". (Grönlund et al 2018).…”
Section: The Development Of New Learning Environmentsmentioning
confidence: 99%
“…Unlike digital resources, which focus on limited areas, cDTB create the conditions for the entire learning environment and for how learners will engage with the curriculum content. Even though cDTB are much more up-to date than traditional books and accept inclusion of content and tools by the teacher, the fact that they provide both a comprehensive content and communication tools pertinent to creating a digital learning environmentthe rules and limitations for interaction among teachers and studentsgives them a prominent role in school, as they have the potential to serve as powerful tools for the teacher and learner (Rodríguez et al 2015;Grönlund et al 2018). In relation to other digital resources, such as websites "2.0" and learning management systems with various features and tools, digital textbooks are designed to provide pupils with some form of quality warranted content in relation to the set learning outcomes of a particular school subject.…”
Section: The Development Of New Learning Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of digital tools requires new ways of thinking and teaching, advanced training programmes. Something more than digital tools is needed to implement e-textbooks (Gronlund, Wiklund & Boo, 2018). A professional development course has shown that e-textbooks allow a teacher to use digital instruments and new approaches and prompt creative reasoning and argumentation processes (Swidan, & Abu-Abdoon, 2018).…”
Section: Research Focusmentioning
confidence: 99%